Analisis Kualitas Instrumen Tes Hasil Prestasi Belajar Pada Mata Pelajaran Bahasa Indonesia Kelas 5 SD Negeri Songgom 05 - Warto Warto (LPPM Politeknik Pratama, 2023)
This study aims to analyze the quality of the learning achievement test instrument in grade 5 Indonesian at SDN Songgom 05. This research is important to ensure that the test instrument used in the school has adequate quality in measuring student achievement. The research method used is descriptive research. Data were collected through direct observation of the test instruments used in grade 5 at SDN Songgom 05. The test instruments analyzed included the questions used in the Indonesian language learning achievement test. The collected data were analyzed using descriptive analysis techniques to evaluate the quality of the test instruments. The results of the analysis showed that the learning achievement test instruments for grade 5 Indonesian at SDN Songgom 05 had generally good quality. The test questions show accuracy in measuring students' ability to understand Indonesian material. However, there are some weaknesses that need to be corrected, such as the existence of some questions that are unclear in writing or ambiguous instructions. Based on the results of the analysis, it is suggested to make improvements to the Indonesian language learning achievement test instrument for grade 5 at SDN Songgom 05. These improvements can be in the form of improvements clearer writing of questions and sharpening instructions in the test instrument. In addition, it is necessary to try out the test instruments periodically to ensure that their quality is maintained and relevant to the applicable curriculum. This research makes an important contribution in improving the quality of the Indonesian language learning achievement test instruments at SDN Songgom 05. It is hoped that the results of this study can become a reference for schools in improving test instruments and increasing the effectiveness of measuring student achievement.